Microscopic Evaluation of 3D-Printed Materials Surface and Characteristic Microstructure - Fousova, Michaela; Vojtech, Dalibor; Fojt, Jaroslav (Manufacturing Technology Journal, 2016)
Selective laser melting (SLM) is one of additive manufacturing technologies capable of processing metallic materials. The quality of final product is influenced by a variety of parameters. Although this technology has been studied intensively for several years, the optimal setting is still in search as these parameters vary with different materials, different designs and alike. The layer-by-layer manufacturing approach brings about several characteristic features. Therefore, this study is focused on observation of characteristic microstructure evolution, resulting surface morphology and changes in surface chemistry when SLM is applied in processing of titanium alloy Ti-6Al-4V and AISI 316L stainless steel. As these materials represent most widely used implantable biomaterials, their surface properties are of particular importance.
Keywords: 3D printing; SLM; AISI 316 L; Ti-6Al-4V; surface evaluation